Changes of emphysema parameters over the respiratory cycle during free breathing: preliminary results using respiratory gated 4D-CT - Ley-Zaporozhan, Julia; Weinheimer, Oliver (COPD, 2017)
The purpose of this research was to evaluate respiratory gated CT of the lung in patients with COPD for analysis of parenchymal characteristics who were potential candidates for volume reduction surgery. Eleven patients with clinically known emphysematous disease underwent a respiratory gated, free-breathing 64-multislice-CT (Aquilion 64, Toshiba). Retrospective image reconstruction was performed similar to cardiac CT at every 10% of the respiratory loop, resulting in 10 complete volumetric datasets at 10 equidistant time points. All images were transferred onto a PC for calculation of the total lung volume, emphysema volume, emphysema index, and mean lung density. Complete datasets could be successfully reconstructed in all patients. The mean lung volume increased from 6.9 L to 7.5 L over the respiratory cycle. Emphysema volume increased from 1.6 L to 2.0 L and emphysema index from 22.6% to 26.5% from expiration to inspiration. In conclusion, respiratory gated chest 4D-CT allows for combined morphologic and functional image analysis, which can provide new insight into functional impairment and individual treatment planning.